Usability of an interactive board game as therapy tool in children with speech sound disorders - Hasherah Mohd Ibrahim,; Cheah, Hazel Bee Leng (Penerbit Universiti Kebangsaan Malaysia, 2021)
Speech sound disorders adversely affect speech intelligibility. It is important to address speech errors early to reduce the impact on long term communication skills. Parental involvement has been shown to increase the effectiveness of speech therapy because parents were able to carry out speech therapy tasks consistently with their children in the comfort of their own homes. This study aimed to explore the usability of an interactive board game as therapy tool in children with speech sound disorders. In Phase I, market survey and website search regarding existing board games were conducted. In Phase II, board game prototypes using the motor approach for speech intervention were developed. Finally, in Phase III, the usability of the board game was examined. Nineteen respondents comprising eight experienced speech-language therapists and eleven parents of children diagnosed with speech sound disorder participated in the study. Participants used the interactive board game with a child with speech sound disorder for a period of one week and completed a questionnaire. Findings show that majority of the participants (94.7%) were satisfied with the board game as a tool for speech therapy. Additionally, 89.4% of the participants agreed that the board game is fun, and all children choose to play the board game again. Suggestions to improve the board game were documented. Further research is warranted to examine the efficacy of this approach on speech therapy outcomes.